Nuclease assisted target recycling and spherical nucleic acids gold nanoparticles recruitment for ultrasensitive detection of microRNA. (1st February 2016) - Miao, Peng; Tang, Yuguo; Wang, Bidou; Jiang, Chengmin; Gao, Liqian; Bo, Bing; Wang, Jue
Graphical abstract: Highlights: An ultrasensitive detection method for microRNA is developed. Duplex specific nuclease assisted target recycling is involved. Spherical nucleic acids gold nanoparticles recruitment is employed for the signal output. Homology microRNA family members are demonstrated to be successfully distinguished. Abstract: Highly sensitive and selective quantification of microRNAs are critical for microRNA discovery, disease diagnostics and theranostics. We herein report a proof-of-concept demonstration of an electrochemical biosensor for microRNA assay based on nuclease assisted target recycling and spherical nucleic acids gold nanoparticles (AuNPs) recruitment. Duplex specific nuclease (DSN) is employed to cleave single-stranded DNA1 probes on the electrode surface via the hybridization of DNA1 and target microRNA. The regenerated single-stranded microRNA can help digest a large number of DNA1 probes, which decreases the efficiency of DNA2 modified AuNPs recruitment by hybridization of complementary sequences. Thereby, the level of target microRNA is negatively related to the amount of electrochemical species which are bound to DNA2. Through the dual amplification of DSN and AuNPs, high sensitivity is achieved. Homology microRNA family members are also demonstrated to be successfully distinguished. Additionally, the performance of the developed method for microRNA assay in human samples is excellent, confirming its practical utility. Therefore, this method is efficient for the quantification of microRNA and may assist public health agencies for the control and prevention of certain diseases.